The Role of Red Music-Assisted Physical Exercise in Guiding Students' Abnormal Psychology - Ke Tian, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Contemporary college students are inevitably subject to both external and internal influences, particularly from the realm of online information, in their academic pursuits and personal lives. To investigate the influence of auditory stimuli on the formation of students' aberrant cognitive processes during physical activity. A total of 1084 middle school students underwent measurements using the SCL-90, GSES, and revised PARS-3 scales. The aim was to examine the impact of physical activity on the physical and mental well-being of middle school students. The statistical software AMOS was utilised to test this hypothesis, and a theoretical framework was developed to investigate the mechanisms underlying physical and mental well-being. Physical activity. The social statistical analysis software packages SPSS17.0 and AMOS17.0 were utilised to examine and handle anomalous data and missing data for statistical analysis. Physical activity and self-efficacy both have varying degrees of negative effects on middle school students' physical and mental pleasure (r2 = 0.094, P 0.01). The equation model demonstrates that the path coefficient of the good fitness index, the amount of physical activity, regular exercise, and independence determine the impact of physical activity on middle school students' physical and mental pleasure. This study establishes a correlation between physical activity, self-efficacy, and both physical and mental enjoyment in middle school students across several aspects. It is anticipated that this research will provide valuable insights for physical activity promotion and education among middle school students. The objective of sports research is to enhance individuals' physical and mental well-being by investigating various forms of exercise and their optimal execution. This study aims to gather self-awareness insights and foster personal growth while also contributing to the regulation of physical and mental health. This diverges from the examination of behavioural modification in psychology and behavioural investigations centred on the intrinsic attributes of "perception attitude behaviour" and social exchange theory.